Correlates of climate change distress: the difference to general distress - Beckord, Jil; Gebhardt, Nadja; Nikendei, Christoph; Krakowczyk, Julia Barbara; Skoda, Eva-Maria; Teufel, Martin; Bäuerle, Alexander (International journal of clinical and health psychology, 2025)
Introduction - Climate change has significant consequences on mental health, which are summarized under concepts like eco-anxiety or climate change distress. However, these recently developed concepts still suffer from a lack of clarity. - Aim - The aim of this study is to improve the conceptual clarity of climate change distress through analysing its’ correlations with various psychological and demographic factors. In this context, the specific associations of climate change distress are compared to those of general distress. - Methods - In a cross-sectional study N = 1000 participants completed an online questionnaire. Climate change distress was assessed using the ‘Climate Change - Man-Made Disaster-Related Distress Scale’. General distress was assessed using the Distress Thermometer, the Generalized Anxiety Disorder scale, and the Patient Health Questionnaire. Several measurement instruments were examined as possible correlates. The outcomes were investigated using multiple linear regression models. - Results - Relevant correlates of climate change distress included trust in government to handle climate change and several emotion regulation strategies. The associated factors of general distress were distinct from those of climate change distress, such as gender and sense of coherence. - Discussion - The results suggest that the correlates of climate change distress differ from those of general distress. This implies that climate change distress and general distress are two related, however distinct constructs. The associated factors can be promising targets for psychotherapy and intervention strategies.